Finding America's voice : a strategy for reinvigorating U.S. public diplomacy - Peterson, Peter G.; Bloomgarden, Kathy F. (Kathy Finn), 1949-; Sieg, Jennifer; Herbstman, Sharon (Council on Foreign Relations, 2003)
The world's opinion of the United States and of U.S. policy has plummeted in the wake of the war in Iraq. The resulting widespread anger, fear, and mistrust, warns this timely report of the independent Task Force on Public Diplomacy, are creating immediate and long-term problems for the United States that must be addressed.